The Believer: Alien Encounters, Hard Science, and the Passion of John Mack by Ralph Blumenthal - Bullard, Eddie (Journal of Scientific Exploration, 2022)
I remember the golden era of UFO abduction research. In 1966 John G. Fuller published The Interrupted Journey and suddenly everyone seemed to know the strange story of Barney and Betty Hill taken from their car by aliens and subjected to medical examinations aboard a flying saucer. The whole town talked about it, so did the whole country. Only ufologists held back, having learned the hard way that the more sensational a UFO story sounded, the more likely it stood on evidential legs too slender to support it. UFOs enjoyed newsworthiness and unaccustomed respect this year; it was no time to puncture the swelling goodwill by falling for a fake, fantasy, or honest mistake (Bullard 2018).            Still, this case was different.  The Hills were highly respected in their community, Fuller was a Saturday Review columnist, and Dr. Benjamin Simon, the psychiatrist who recovered memories of the Hills’ period of missing time by means of hypnosis, was a pillar of his profession.  Incredible as the story sounded, it unfolded with credible verisimilitude.  It told us more about the aliens and their spaceship than any previous trustworthy report.  It even made sense according to the prevailing conception that aliens arrived as explorers like our astronauts, their mission to observe, collect soil samples, and doubtless to study the numerous large mammals having the technology to ride around in four-wheeled machines.